The biology of Canadian weeds. 108. Erucastrum gallicum (Willd.) O.E. Schulz - Warwick, Suzanne I.; Wall, David A. (Canadian Journal of Plant Science, 1998)
A review of biological information is provided for Erucastrum gallicum (Willd.) O.E. Schulz. A European native, it was introduced into Canada and the United States in the early 1900s and spread rapidly along the railroads. The species occurs in all the provinces and the Northwest Territories and is particularly abundant in the Prairie provinces and mid-western United States. It is a summer annual, rarely a winter annual or biennial species, and is characterized by high reproductive output. Plants occur most commonly on waste ground and along roadsides and railroads, followed by agricultural fields. Erucastrum gallicum is of allopolyploid origins (n = 15, 7 + 8 chromosomes), and contains a single multi-locus isozyme genotype. The species is a close relative of Brassica and is capable of limited genetic exchange with the canola species, B. rapa and B. napus. The possible transfer of genes from transgenic canola varieties to Erucastrum gallicum poses a remote, but potential, environmental risk. Populations of Erucastrum gallicum, including both Old World and North American populations, constitute a valuable germplasm resource as potential sources of beneficial agronomic traits, such as disease resistance for canola crop improvement. Key words: Dog mustard, Erucastrum gallicum, weed biology, risk assessment, germplasm, canola